2021
DOI: 10.1002/adma.202101698
|View full text |Cite
|
Sign up to set email alerts
|

A Gas‐Steamed MOF Route to P‐Doped Open Carbon Cages with Enhanced Zn‐Ion Energy Storage Capability and Ultrastability

Abstract: Carbon micro/nanocages have received great attention, especially in electrochemical energy‐storage systems. Herein, as a proof‐of‐concept, a solid‐state gas‐steamed metal–organic‐framework approach is designed to fabricate carbon cages with controlled openings on walls, and N, P dopants. Taking advantage of the fabricated carbon cages with large openings on their walls for enhanced kinetics of mass transport and N, P dopants within the carbon matrix for favoring chemical adsorption of Zn ions, when used as car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 61 publications
0
90
0
1
Order By: Relevance
“…This indicates the existence of PO x groups and P-C units in the carbon skeleton. 21 The S 2p spectrum could be tted to three peaks at 163.9, 165.2 and 168.0 eV, which are associated with S 2p 3/2 of C-S, S 2p 1/2 of C-S and C-SO x -C bonding (Fig. 2i), respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This indicates the existence of PO x groups and P-C units in the carbon skeleton. 21 The S 2p spectrum could be tted to three peaks at 163.9, 165.2 and 168.0 eV, which are associated with S 2p 3/2 of C-S, S 2p 1/2 of C-S and C-SO x -C bonding (Fig. 2i), respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Zhang et al 17 designed a hollow carbon polyhedron using ZIF-8 as the template, and the as-prepared electrode exhibited good stability. In addition, carbon materials doped with heteroatoms, such as nitrogen (N), 18,19 sulfur (S), 20 phosphorus (P) 16,21,22 and boron (B), 23 have attracted increasing attention due to their excellent performance and potential applications in energy storage. The doping of heteroatoms into carbon materials is benecial to develop more defective sites, which increase active sites for ion de/adsorption and electronic conductivity of the carbon electrode; 24,25 it also improve the wettability of the electrolyte, which is conductive to the electrolyte permeation.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the commercial AC, many PCs electrode materials can be fabricated through various methods, like template method [111][112][113] and pyrolysis method [108,[114][115][116]. As for the pyrolysis methods, the precursor is a significant part of synthesizing high-quality PC electrode materials.…”
Section: Hssa Carbon Electrodementioning
confidence: 99%
“…Lu et al reported molten salt-assisted synthesis of pitch-derived PCs cathodes for Zn//Cap ZHSCs while Guan et al proposed bamboo-derived PCs cathodes with superb stability when employed in ZHSCs (96% capacity retention after 90,000 cycles) [114,115]. Moreover, Xu et al and Shen et al reported a MOF route for fabricating PCs electrode materials, the ZIF-8-derived PCs presented an splendid performance of 225 mAh g −1 at 0.1 A g −1 and remained 135.5 mAh g −1 at 1 A g −1 [98,116]. As depicted in Fig.…”
Section: Hssa Carbon Electrodementioning
confidence: 99%
See 1 more Smart Citation